2016
DOI: 10.1080/09674845.2016.1186310
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile of cerebrospinal fluid in patients with multiple sclerosis using two dimensional gel electrophoresis

Abstract: a faculty of medicine, department of clinical Pathology, alexandria university, alexandria, egypt; b chru de montpellier and université de montpellier, irmB, laboratoire de Biochimie Protéomique clinique, montpellier, france; c faculty of medicine, department of neuropsychiatry, alexandria university, alexandria, egypt; d faculty of medicine, department of anesthesia and surgical care, alexandria university, alexandria, egypt ABSTRACT Background: Multiple sclerosis (MS) is a highly heterogeneous disease affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Due to the variety and non-specific nature of presenting signs and symptoms, the diagnosis of multiple sclerosis (MS) is hampered by lack of specific markers. Hassan and colleagues [22] used a proteomic approach with two-dimensional electrophoresis and MALDI-TOF/TOF mass spectroscopy to probe cerebro-spinal fluid from MS patients and controls. Four proteins (alpha-1-antichymotrypsin, prostaglandin-H2 D-isomerase, desmoplankin and hornerin) where present in significantly higher levels in the MS patients, suggesting these may be used as potential CSF markers of this disease.…”
Section: Haematologymentioning
confidence: 99%
“…Due to the variety and non-specific nature of presenting signs and symptoms, the diagnosis of multiple sclerosis (MS) is hampered by lack of specific markers. Hassan and colleagues [22] used a proteomic approach with two-dimensional electrophoresis and MALDI-TOF/TOF mass spectroscopy to probe cerebro-spinal fluid from MS patients and controls. Four proteins (alpha-1-antichymotrypsin, prostaglandin-H2 D-isomerase, desmoplankin and hornerin) where present in significantly higher levels in the MS patients, suggesting these may be used as potential CSF markers of this disease.…”
Section: Haematologymentioning
confidence: 99%
“…In the present study, we aimed to analyze limitations of 2D-DIGE in proteomic studies of the CSF in order to explore possible reasons why results of previous studies in MS patients have been so controversial [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. It seems obvious using 2D-DIGE for identification of proteins in the CSF of MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…After separation proteins can be picked from 2DE gels and identified e.g., by mass spectrometry. In MS, proteins of the cerebrospinal fluid (CSF) may be of major interest in order to identify possible candidate proteins which are up- or downregulated in comparison to healthy subjects [ 5 ]. There are some studies investigating CSF-proteins of MS patients by 2DE or two-dimensional difference gel electrophoresis (2D-DIGE) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review thus investigated whether currently identified protein species can be considered as biomarkers for MS, using comprehensive literature mining and bioinformatics to anchor the analysis. During the last two decades, proteomic approaches were used to assess various samples from animal models of MS (e.g., experimental autoimmune encephalomyelitis, EAE and cuprizone, CPZ), as well as from MS patients [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. However, there do not appear to be any critical systematic reviews of the protein species identified from these studies.…”
Section: Introductionmentioning
confidence: 99%